INTERVENSI PELATIHAN KOMUNIKASI ASERTIF DAN PERSUASIF PADA KOMUNITAS JURU PEMANTAU JENTIK RW 07 - Brenda Asnaputri Bu’ulolo; Christie Anjelique Latif; Christie Clara Pingkan Poluakan; Keysha Zaretha Adhisty Layla; Samira Estu Wijidani; Vanessa Julianne Manalu; Penny Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2026)
The number of Dengue Hemorrhagic Fever cases in Indonesia has reached 10,752 and remains a public health issue requiring greater attention from both the government and the community. The Mosquito Monitoring Community (Jumantik) serves as a community group responsible for monitoring and supervising local residents to ensure their environment is free from mosquito larvae. In carrying out their duties, the cadres are expected to provide education through public outreach so that residents can understand strategies to prevent mosquito larvae inside their homes. However, in practice, some residents refuse home inspections and show indifference toward cleanliness. Additionally, the importance of maintaining a larva-free home is not well understood by many residents. The communication approaches used by the cadres to engage with the community also often result in discomfort among the residents. Furthermore, Jumantik cadres do not receive training on how to properly conduct educational outreach. Therefore, an intervention in the form of assertive and persuasive communication training is necessary to improve their communication skills. Follow-up actions such as coaching and the distribution of questionnaires were also carried out to monitor progress in communication skills after the training. The results showed positive development in the communication abilities of the Jumantik cadres, especially in persuasive communication. Representatives of neighborhood associations (RT) and residents also reported improvements in the communication skills of the Jumantik cadres.